2000
DOI: 10.1007/bf03343713
|View full text |Cite
|
Sign up to set email alerts
|

Activin A stimulates insulin secretion in cultured human pancreatic islets

Abstract: Activin A is a dimeric glycoprotein showing a high sequence homology with transforming growth factor-beta (TGF-beta) and playing autocrine/paracrine actions in reproductive tissues. However, since the synthesis of activin is ubiquitous it may have a role in regulating cell growth and differentiation in several tissues. Previous studies showed that activin A is expressed by insulin-positive B cells of human pancreatic islets, and women with gestational diabetes have higher serum activin A levels than healthy pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
56
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(59 citation statements)
references
References 21 publications
2
56
1
Order By: Relevance
“…Acute activin A treatment of cultured rat and human islets was reported to increase insulin secretion [21,22]; however acutely treated MIN6 cells did not show increased secretion [29]. In our study, activin A had no acute stimulatory effect on glucose-stimulated insulin secretion in perifused isolated mouse islets, while prolonged activin A treatment significantly decreased insulin secretion.…”
Section: Discussioncontrasting
confidence: 71%
See 2 more Smart Citations
“…Acute activin A treatment of cultured rat and human islets was reported to increase insulin secretion [21,22]; however acutely treated MIN6 cells did not show increased secretion [29]. In our study, activin A had no acute stimulatory effect on glucose-stimulated insulin secretion in perifused isolated mouse islets, while prolonged activin A treatment significantly decreased insulin secretion.…”
Section: Discussioncontrasting
confidence: 71%
“…Insulin secretion was also 14.5% lower from activin Atreated human islets (M. Szabat, unpublished data). Since previous studies have reported that acute activin A treatment of cultured rat and human islets increased insulin secretion [21,22], we also examined the acute effects of 4 nmol/l activin A in perifused mouse islets (Fig. 5c).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier studies indicated that activin A enhances insulin secretion [12,13,37]. However, more recent work reported that activin A has either no effect [4] or in fact decreases [15,16] GSIS by islets.…”
Section: Discussionmentioning
confidence: 98%
“…Immunohistochemical studies have localised activin A predominantly to alpha cells, while activin B was shown to be expressed by both alpha and beta cells [4]. Earlier work showed that exogenous activin A can increase the cytoplasmic free Ca 2+ concentration and stimulate insulin secretion in human and rat pancreatic islets, even at low levels of ambient glucose [12][13][14]. Those results have been challenged by more recent studies indicating that in mouse islets, activin A either has no effect [4] or may in fact decrease GSIS [15,16].…”
Section: Introductionmentioning
confidence: 99%